Exploration of basil (Ocimum basilicum) essential oil profiles using E-nose and GC–MS combined with GC-O and inhalation effects on the human EEG topography and tomography (s-LORETA) and blood pressure - Seong Jun Hong; Da-Som Kim; Seong Min Jo; Sojeong Yoon; Hyangyeon Jeong; Moon Yeon Yoon; Jae Kyeom Kim; Young Jun Kim; Eui-Cheol Shin (Journal of Functional Foods, 2024)
This study aimed to investigate the changes in human EEG activity, Brodmann area, and blood pressure during basil essential oil inhalation. Seven odor-active compounds were detected by GC–MS combined with GC–olfactometry, and three abundant volatile compounds were detected by electronic nose. Linalool was simultaneously regarded as a major volatile compound. The systolic and diastolic blood pressures and pulse levels showed a decreasing trend during BEO inhalation. The relative beta and gamma waves in most brain regions changed during BEO inhalation. The gamma waves decreased, whereas the beta waves increased during BEO inhalation. In particular, the beta waves in the left frontal and right parietal regions and Brodmann area 38 significantly increased during inhalation using sLORETA. Accordingly, these results were highly associated with reduced stress responses by decreased gamma waves, blood pressures, and pulse levels and improved language-related functions by the increased beta wave at Brodmann area 38.